Prospective Clinical Trial for Septic Arthritis: Cartilage Degradation and Inflammation Are Associated with Upregulation of Cartilage Metabolites. (5th September 2016) - Schmal, Hagen; Bernstein, Anke; Feucht, Matthias J.; Erdle, Benjamin; Pestka, Jan M.; Pham, That Minh; Kubosch, Eva Johanna
Abstract : Background . Intra-articular infections can rapidly lead to osteoarthritic degradation. The aim of this clinical biomarker analysis was to investigate the influence of inflammation on cartilage destruction and metabolism. Methods . Patients with acute joint infections were enrolled in a prospective clinical trial and the cytokine composition of effusions (n = 76 ) was analyzed. Characteristics of epidemiology and disease severity were correlated with levels of cytokines with known roles in cartilage turnover and degradation. Results . Higher synovial IL-1 β concentrations were associated with clinical parameters indicating a higher disease severity (p < 0.03 ) excluding the incidence of sepsis. Additionally, intra-articular IL-1 β levels correlated with inflammatory serum parameters as leucocyte counts (LC) and C-reactive protein concentrations (p < 0.05 ) but not with age or comorbidity. Both higher LC and synovial IL-1 β levels were associated with increased intra-articular collagen type II cleavage products (C2C) indicating cartilage degradation. Joints with preinfectious lesions had higher C2C levels. Intra-articular inflammation led to increased concentrations of typical cartilage metabolites as bFGF, BMP-2, and BMP-7. Infections with Staphylococcus species induced higher IL-1 β expression but less cartilage destruction than other bacteria. Conclusion . Articular infections have bacteria-specific implications on cartilage metabolism. Collagen type II cleavage products reliably mark destruction, which is associated with upregulation of typical cartilage turnover cytokines. This trial is registered withDRKS00003536, MISSinG.